Religious Habitus Formation Through Madrasah-Pesantren Collaboration: A Sociological Analysis - Irfan Musonif; Annisa Nur Baeti; Muhamad Ibnu Athoillah; Donny Khoirul Azis; Fatur Fahrezi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study addresses the limited integration between formal Islamic education (madrasah) and pesantren in shaping students’ religious character, which remains insufficiently explored in the sociology of Islamic education. Existing studies tend to examine these institutions separately, with little attention to how their collaboration contributes to the formation of religious habitus through sustained social processes. This research aims to analyze how madrasah–pesantren collaboration facilitates the formation of students’ religious habitus. A qualitative case study was conducted at MTs Al-Ma’arif Rakit, involving its partnership with two Islamic boarding schools. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that collaboration between madrasah and pesantren creates an integrated social education system in which religious values are internalized through habituation, role modeling, and continuous social interaction. The formation of religious character operates across three interconnected dimensions: collective moral consciousness (Durkheim), habitus formation and reproduction (Bourdieu), and social self-construction (Mead). Notably, the study finds that religious habitus is reproduced not only among boarding students but also among non-residential students through shared social environments. This study contributes theoretically by extending the concept of religious habitus within a collaborative educational context, and practically by proposing a madrasah–pesantren model for integrative Islamic character education.